2020
DOI: 10.1002/jbmr.4649
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning–Derived Acetabular Dysplasia and Cam Morphology Are Features of Severe Hip Osteoarthritis: Findings From UK Biobank

Abstract: The contribution of shape changes to hip osteoarthritis (HOA) remains unclear, as is the extent to which these vary according to HOA severity. In the present study, we used statistical shape modeling (SSM) to evaluate relationships between hip shape and HOA of different severities using UK Biobank DXA images. We performed a cross-sectional study in individuals with left hip dual-energy X-ray absorptiometry (DXA) scans. Statistical shape modeling (SSM) was used to quantify hip shape. Radiographic HOA (rHOA) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 34 publications
0
28
2
Order By: Relevance
“…Modelling changes are recognised by Croft grading in late-stage HOA (11), however we are not aware of any previous reports describing cam morphology as a specific feature of HOA. That said, in the same set of DXA images, we have recently found that hip shape changes suggestive of cam morphology are associated with more severe forms of HOA (50).…”
Section: Discussionmentioning
confidence: 67%
“…Modelling changes are recognised by Croft grading in late-stage HOA (11), however we are not aware of any previous reports describing cam morphology as a specific feature of HOA. That said, in the same set of DXA images, we have recently found that hip shape changes suggestive of cam morphology are associated with more severe forms of HOA (50).…”
Section: Discussionmentioning
confidence: 67%
“…While computer vision approaches to extract and analyze DXA scan derived phenotypes are not themselves novel 16,17,29,30 , this work is amongst the first to use this approach on a disease for which diagnosis is primarily radiographic, to demonstrate that having a quantitative endophenotype that captures additional information about variation in disease severity improves power for genomic and epidemiological analysis. Although not based on the imaging data, two novel phenotyping methods leveraging deep learning to impute missing data in the UKB and to generate disease liability scores from binary case-control data in the EHR have shown significant boosts in statistical power for genomic studies 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of these developments in computer vision, recent genetic studies have successfully applied these methods to generate image derived phenotypes (IDPs) of distribution of body fat, heart structure, liver fat percentage, and brain morphology, and have linked these novel traits with genome-wide significant loci [10][11][12][13][14] . While some recent studies on musculoskeletal disease employ these novel phenotyping approaches [15][16][17] , neither these nor the studies on other traits have specifically investigated how generating quantitative IDPs that underlie binary disease status could be used to improve power for gene discovery at biobank scale.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative explanation is that the femoral neck is widened as part of, or in parallel to the onset of HOA rather than the widened femoral neck causing HOA. Recent evidence from studies using SSM suggests a wider femoral neck is associated with more severe HOA and separately a genetic study suggested that a genetic predisposition to HOA led to cam-like changes at the femoral head (11,26,27). Both these Hip geometry and its associations with hip osteoarthritis studies suggest that hip shape is associated with but might not be a cause of HOA which has treatment implications.…”
Section: Discussionmentioning
confidence: 99%
“…; https://doi.org/10.1101/2023.03. 28.23287740 doi: medRxiv preprint Hip geometry and its associations with hip osteoarthritis suitable for ascertaining both hip shape and radiographic HOA (rHOA) measures (10,11). In addition, DXA scans involve lower doses of radiation than traditional radiographs, offering the potential for use in screening.…”
Section: Introductionmentioning
confidence: 99%